Penerapan Model Project Based Learning Untuk Meningkatkan Kreativitas Dan Hasil Belajar Ipas Siswa Kelas V SD Katolik St. Joseph Sarongsong - Yeci J. Samauling; Zoya F. Sumampow; Yusak Ratunguri (Peneliti.net, 2026)
This study aims to improve students' creativity and learning outcomes in Natural and Social Sciences, specifically the topic of Human Digestive Organs, through the application of the Project Based Learning (PjBL) model in fifth grade students of SD Katolik St. Joseph Sarongsong. The method used is Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 16 students, including 9 females and 7 males. The results show that the implementation of the Project Based Learning (PjBL) model effectively improves students' creativity and learning outcomes. The average creativity level in the first cycle reached 63.28% in the medium category and increased to 81.64% in the high category in the second cycle. In terms of learning outcomes in the cognitive domain, the average score in the first cycle was 66.25 with a classical completeness of 43.75%, which improved to 87.81 with 87.5% completeness in the second cycle. In the affective domain, students’ attitudes in cycle I had not fully met the learning targets but showed improvement in cycle II until the objectives were achieved. In the psychomotor domain, learning outcomes increased from 64.06% in cycle I to 85.15% in cycle II. Based on these findings, it can be concluded that the PjBL model is effective in enhancing students’ creativity and learning outcomes in science learning.